2000
DOI: 10.1038/sj.ejcn.1600967
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intakes of vegetarian populations in France

Abstract: Objective: To assess food behaviour and determine nutritional intakes of various vegetarian populations in France. Design: A ®ve-day self-administered food record which was mailed to members of the three principal French vegetarian organisations. Subjects: 145 subjects, aged 7 ± 87 y; 94 classical vegetarians (19% of those contacted), 34 Hindu lactovegetarians (17% of those contacted) and 17 macrobiotic (34% of those contacted). Setting: The survey was conducted between March 1997 and July 1997 in France. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
4
20
1
Order By: Relevance
“…However, the realism of such scenarios is questionable since the prevalence of vegetarianism is quite low in industrialized countries (e.g. estimated to be approximately 2 % in the French (46) and US (47) populations). In addition, some studies suggest that a large proportion of the population is not yet ready to consume a fully plantbased diet (48,49) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the realism of such scenarios is questionable since the prevalence of vegetarianism is quite low in industrialized countries (e.g. estimated to be approximately 2 % in the French (46) and US (47) populations). In addition, some studies suggest that a large proportion of the population is not yet ready to consume a fully plantbased diet (48,49) .…”
Section: Discussionmentioning
confidence: 99%
“…[6] Epidemiological studies on vegetarians show that appropriately planned vegetarian diets are healthy and nutritionally adequate. [7][8][9][10][11] Compared to non-vegetarian (NV) diets, V diets can provide several health benefits. [12][13][14][15] However, these health benefits in vegetarians may be influenced by other non-dietary practices.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that vegetarians in France believe their diet is an answer to nutritional and medical problems, and it is a way to return to a more natural life. However, the primary reason for the rejection of meat is because of the cruelty to animals and a crusade for health (Leblanc, Yoon, Kombadjian, & Verger, 2000). Disease prevention also played a role in diet choices of female vegetarians studied.…”
Section: Reasons For Choosing a Vegetarian Dietmentioning
confidence: 99%
“…Heme iron intake of French vegetarians accounted for 0.2 mg per day in the lacto-ovo-vegetarians, and none in the lacto-vegetarians and vegans (p<0.01) (Leblanc et al, 2000). Consumption of iron derived from the different sources of food is important because heme and nonheme iron have different bioavailability (Mahan & Escott-Stump, 2004), which is discussed later in the Review of Literature.…”
Section: Types Of Ironmentioning
confidence: 99%
See 1 more Smart Citation